FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN PERTAMBANGAN DI BEI PERIODE 2008-2010 - YOVITA SARI LIE, NELLA (Berkala Ilmiah Mahasiswa Akuntansi)
Financial reports are one source of information that is often used by the users of financial statements. The benefits of information in financial statements can be reduced over time, if the company did not submit financial statements on time to the public. Hence the timeliness of financial reporting is essential, so this study aims to examine the factors that influence the timeliness of financial reporting. Form of quantitative research design with hypotheses. Independent variables used are liquidity, profitability, firm size, reputation KAP, opinions public accountants, managerial ownership and public ownership. Object of research is a mining company in Indonesia Stock Exchange 2008-2010 period. Total observations used in the study as much as 69 samples were selected by purposive sampling technique. Source data obtained from the IDX website in the form of secondary data. Techniques of data analysis using logistic regression. The results show that liquidity, firm size, managerial ownership and public ownership affect the timeliness of financial reporting. Meanwhile, profitability, reputation and opinion KAP public accountant does not affect the timeliness of financial reporting.